Vitamin D Supplementation does not Effect Adiposity in Healthy Adults - Mehmood, Zujaja-Tul-Noor Hamid; Papandreou, Dimitrios (Arab Journal of Nutrition and Exercise (AJNE), 2017)
Introduction: Vitamin D is crucial for skeletal and extraskeletal health outcomes as Vitamin D binding receptors are located through out body, and epidemiological data supports its link with many conditions. Data on vitamin D levels and especially Vitamin D supplementation in U.A.E. is essentially inadequate. Design: Subjects (n=20) in this 1 month prospective study were given 2000 IU of daily Vitamin D without any special dietary or physical activity changes. Anthropometrics (weight, waist circumference, hip circumference), Vitamin D/ Calcium food frequency questionnaire and 24 –Hour recall were collected. Results: Mean age of subjects was 28.7 years, and baseline mean serum Vitamin D level of 17.5 ng/mL ±6.47. It increased Vitamin D serum levels by a mean of 6.76 ng/mL. Hip Circumference also reduced statistically significantly by moderate 2% (p 0.03 ±0.59), Conclusion: Vitamin D supplementation moderate dose daily can be pivotal in acquiring health benefits and reducing adiposity related factors. However, this surely calls for further investigation for longer period.